GE_GERICHTE P/4337/2025 vom 28. Mai 2025 - GE Cour de justice (2025)
ORDONNANCE DE NON-ENTRÉE EN MATIÈRE;ACCIDENT DE LA CIRCULATION;ANIMAL;DOMMAGES À LA PROPRIÉTÉ(DROIT PÉNAL) | CPP.310.al1.leta; CP.144; LPA.26